2014
DOI: 10.1063/1.4901721
|View full text |Cite
|
Sign up to set email alerts
|

Shear rheology and structural properties of chemically identical dendrimer-linear polymer blends through molecular dynamics simulations

Abstract: We present nonequilibrium molecular dynamics (NEMD) simulation results for the miscibility, structural properties, and melt rheological behavior of polymeric blends under shear flow. The polymeric blends consist of chemically identical linear polymer chains (187 monomers per chain) and dendrimer polymers of generations g = 1-4. The number fraction x of the dendrimer species is varied (4%, 8%, and 12%) in the blend melt. The miscibility of blend species is measured, using the pair distribution functions gDL, gL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This is important in tribology since PEF occurs in the entrance region of high pressure, elastohydrodynamic contacts [95]. PEF simulations have been widely used to study polymers flow [96,97] but more rarely for lubricant-sized molecules. Baig et al [98] studied the rheological and structural properties of linear liquid n-alkanes (C 10 , C 12 , C 20 ) using NEMD simulations under PEF.…”
Section: Modified Nemd Algorithmsmentioning
confidence: 99%
“…This is important in tribology since PEF occurs in the entrance region of high pressure, elastohydrodynamic contacts [95]. PEF simulations have been widely used to study polymers flow [96,97] but more rarely for lubricant-sized molecules. Baig et al [98] studied the rheological and structural properties of linear liquid n-alkanes (C 10 , C 12 , C 20 ) using NEMD simulations under PEF.…”
Section: Modified Nemd Algorithmsmentioning
confidence: 99%
“…[34][35][36][37][38][39] A crucial question arises when blending linear chain polymers with these tree-like molecules, and that is under which conditions these species will form a miscible blend. This issue has been partially addressed in our previous paper, 40 in which we showed that since our model dendrimers and linear polymers had an identical chemical nature, the molecular size ratio between the linear and dendrimer molecules is the main parameter influencing their miscibility. All of our blend systems formed miscible blends.…”
Section: Introductionmentioning
confidence: 91%
“…In this way, the penetration of the beads belonging to linear molecules toward the interior of dendrimer molecules is analysed. 40 Fig. 4 compares the g c,DL function for the blend systems 12D187B, 8D187B, and 4D187B atε = 2 × 10 −4 to display the dependence of interpenetration on the dendrimer concentration at fixed dendrimer molar mass.…”
Section: A Structural Analysismentioning
confidence: 99%
See 2 more Smart Citations